Analisa Kelelahan Kerja Berdasarkan Dimensi Swedish Occupational Fatigue Index (SOFI) Pada Pekerja Produksi - Lubis, Siti Rahmah Hidayatullah; Mu’minah, Nuranisa (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2022)
Occupational fatigue is one of the important risk factors related to occupational safety and health for production workers. Production workers are one type of work that experience work fatigue, caused by the high workload, especially because of the demands for high accuracy when working. The purpose of this study was to measure the level of work fatigue in production workers at PT. Sarandi Nugraha. The research method used is cross sectional observation. The research sample was 84 production workers who were selected using the total sampling technique. The instrument used to measure occupational fatigue is the Swedish Occupational Fatigue Index (SOFI) questionnaire which consists of 5 dimensions of fatigue, namely: lack of energy, physical exertion, physical discomfort, lack of motivation and sleepiness. The results showed subjective occupational fatigue on the dimension of lack of energy with a moderate fatigue level (57.14%), the physical exertion dimension with a moderate fatigue level (57.14%), the dimension of physical discomfort with a low fatigue level (52.38%), the dimension of lack of motivation with low fatigue level (58.33%) and sleepiness with low fatigue level (55.95%). So it can be concluded that the perceived occupational fatigue tends to be caused by the physical workload. It is necessary to provide air conditioning that is evenly distributed in each work area, clean and comfortable rest rooms, provide reminders for workers to stretch between jobs.